2022
DOI: 10.3389/fcvm.2021.743257
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Permanent Pacemaker Implantation in Patients After Transcatheter Aortic Valve Replacement in a Chinese Population

Abstract: Background: Permanent pacemaker (PPM) implantation is the main complication of transcatheter aortic valve replacement (TAVR). Few studies have evaluated the requirement for PPM implantation due to ECG changes following TAVR in a Chinese population.Objective: Our study aimed to evaluate the incidence and predictors of PPM implantation in a cohort of Chinese patients with TAVR.Methods: We retrospectively evaluated 39 consecutive patients with severe native aortic stenosis referred for TAVR with a self-expandable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…In a prospective study, Pavlicek et al ( 51 ) reported that postoperative new-onset LBBB (OR: 15.72; 95% CI: 3.05–81.03; p = 0.001) and preoperative bundle-branch block (OR: 11.64; 95% CI: 2.87-47.20; p = 0.001) were independent predictors of high-grade atrioventricular block (HAVB) necessitating PPI after TAVR. Data from a Chinese TAVR cohort indicated that new-onset LBBB ( p = 0.004) and lead I T-wave elevation ( p = 0.016) were the primary predictors of PPI ( 52 ). It was also suggested in some studies that ΔPR (the difference between the postoperative and preoperative PR intervals) was probably an independent predictor of delayed late conduction disorders (≥48 h) after TAVR ( 53 ), with ΔPR > 40 ms linked notably to an increased risk of PPI ( 54 ).…”
Section: Predictors Of Conduction Abnormalities After Tavrmentioning
confidence: 99%
“…In a prospective study, Pavlicek et al ( 51 ) reported that postoperative new-onset LBBB (OR: 15.72; 95% CI: 3.05–81.03; p = 0.001) and preoperative bundle-branch block (OR: 11.64; 95% CI: 2.87-47.20; p = 0.001) were independent predictors of high-grade atrioventricular block (HAVB) necessitating PPI after TAVR. Data from a Chinese TAVR cohort indicated that new-onset LBBB ( p = 0.004) and lead I T-wave elevation ( p = 0.016) were the primary predictors of PPI ( 52 ). It was also suggested in some studies that ΔPR (the difference between the postoperative and preoperative PR intervals) was probably an independent predictor of delayed late conduction disorders (≥48 h) after TAVR ( 53 ), with ΔPR > 40 ms linked notably to an increased risk of PPI ( 54 ).…”
Section: Predictors Of Conduction Abnormalities After Tavrmentioning
confidence: 99%
“…It is of great significance to highlight that the patient should be closely monitored during the procedure for signs of stroke, and the conscious sedation offers a clear advantage on this field. Renal failure is also common after TAVI with contributing factors including preoperative impaired renal function and the amount of contrast used [36]. Additionally, the presence of acute renal injury is a negative prognostic factor in patients undergoing TAVI [5].…”
Section: Complicationsmentioning
confidence: 99%